Experimental evaluation of herbicide use on biodiversity, ecosystem services and timber production trade‐offs in forest plantations. Issue 1 (12th August 2021) - Stokely, Thomas D.; Kormann, Urs G.; Verschuyl, Jake; Kroll, Andrew J.; Frey, David W.; Harris, Scott H.; Mainwaring, Doug; Maguire, Doug; Hatten, Jeff A.; Rivers, James W.; Fitzgerald, Stephen; Betts, Matthew G.
Abstract: The value of non‐commodity ecosystem services provided by forests is widely recognized, but intensive forest management practices are increasing, with uncertain consequences for a multitude of these services. Quantitative relationships among biodiversity conservation, timber production and other ecosystem services remain poorly understood, especially during the early‐successional period of intensively managed forestlands. We manipulated management intensity in regenerating forest plantations to test the prediction that treatments aimed at maximizing timber production decrease biodiversity conservation and non‐timber services. We measured species richness of 3 taxonomic groups and 13 proxies for provisioning, cultural and regulating services within stands randomly assigned to one of the three herbicide application intensities or an untreated control. Herbicides increased allocation of net primary production to crop trees, increasing projected timber volume and revenues at 40‐ and 60‐year harvest ages. Commonly used herbicide prescriptions reduced culturally valued plants by 71%, wild‐ungulate forage by 41%, avian richness by 20% and pollinator floral resources by 42%, the latter being associated with 38% fewer pollinator species. However, agriculturally valued bumblebees, pollination of blueberries, avian‐mediated arthropod control, wild ungulate observations and regulation services tied to forest productivity appeared unaffected by increasing management intensity and timber production. Species richness and flora‐provided services in young forest plantations exhibited strong trade‐offs with projected timber production, whereas post‐treatment vegetation regeneration and site‐level variation likely maintained a range of other services. Although vegetation recovery is important for supporting wildlife and some ecosystem services on industrial forestlands, it is unlikely that any single prescription can optimize both timber and non‐timber benefits to society across managed forest landscapes. Instead, producing different services in discrete portions of the landscape may be necessary. Synthesis and applications . We tested the effects of intensive forest management via herbicides on ecosystem services and found that biodiversity responses and services from early‐successional vegetation trade‐off against timber production. A number of services appeared to be compatible with timber production, although no single prescription optimized the full range of services. Stand‐level biodiversity conservation and a variety of services could potentially be provided by treatment skips and less‐intensive management on productive sites, although it is unlikely that all services can be optimized without landscape‐level planning. Abstract : We tested the effects of intensive forest management via herbicides on ecosystem services and found that biodiversity responses and services from early‐successional vegetation trade‐off against timber production. A number of services appeared to be compatible with timber production, although no single prescription optimized the full range of services. Stand‐level biodiversity conservation and a variety of services could potentially be provided by treatment skips and less‐intensive management on productive sites, although it is unlikely that all services can be optimized without landscape‐level planning.